Assessment of pesticide safety knowledge and practices in Vietnam: A cross-sectional study of smallholder farmers in the Mekong Delta - Galli, Anaïs; Winkler, Mirko S.; Doanthu, Thuy; Fuhrimann, Samuel; Huynh, Tuyen; Rahn, Eric; Stamm, Christian; Staudacher, Philipp; Huynh, Tung Van; Loss, Georg (Informa UK Limited, 2022)
Over the past three decades, the Vietnamese Mekong Delta has experienced a significant increase in agricultural productivity, partly achieved through increased agrochemical use. To abate negative effects on human and environmental health, several national programs were launched to enhance safer pesticide use. This study aimed to assess the patterns and relationships of official sustainable agriculture educational programs, pesticide safety knowledge, and practices of smallholder farmers in the Mekong Delta. A cross-sectional survey was conducted with 400 smallholder farmers from three communes in Thoi Lai district (Can Tho province) from March to May 2020. Twenty-four questions on pesticide safety knowledge and practices were used to identify traits using latent class analysis. Adjusted generalized linear regression was used to assess determinants of pesticide safety knowledge and estimate associations of pesticide safety knowledge with pesticide practices. 96.2% of participants have used at least one WHO class II pesticide during the past year while the use of specific personal protective equipment was limited mainly due to unavailability (37.0%) or discomfort (83.0%). High education (Odds Ratio (OR), 95% Confidence Interval; 3.84, 1.70–9.45), exposure to official educational programs (1.87, 1.13–3.12), peer-to-peer knowledge exchange (3.58, 2.18–6.00), and learning from governmental extension services (2.31, 1.14–4.98) were positively associated with increased pesticide safety knowledge. Compared to poor practices, pesticide safety knowledge was increasingly positively associated with intermediate (1.65, 1.02–2.66) and good pesticide practices (8.96, 2.58–31.12). These findings highlight the importance of school education and educational programs, access to PPE, and addressing discomforts of PPE to improve the protection of farmers from pesticide exposures. Simultaneously, pesticide market authorization processes should be reconsidered to promote the authorization of less toxic products. Further indepth studies on the nature of pesticides used, nonuse of personal protective equipment, and effectiveness of educational programs will further define leverage points for safer pesticide use.